Invesment Assessement on Small Scale Shrimp Fishing Industry for Shrimp Resource Management At North Cirebon and Surrounding Fishing Area, West Java - Dinarwan Dinarwan (Buletin Ekonomi Perikanan, 1993)
Two main issues: - sustainability of shrimp fishing area at North Cirebon and surrounding area and - feasibility of various fishing units were analyzed with the application of bioeconomic model and invesment analysis. It was evident from bioeconomic point of view that exploitation level of shrimp resource in the study area has come to overfishing condition. The implication is that fishing effort on shrimp should be corrected. The correction should not be based solely on biological consideration but also on the financial/invesment assessment.